The Urgency of Implementing Patent Commercialization Regulations Based on the Patents Law No. 13 of 2016 in Comparison with the South Korean Invention Promotion Act No. 19495 of 2023 - Danastri, Aprilia; Amirulloh, Muhamad; Muchtar, Helitha Novianty (Dinasti Research, 2025)
Patent commercialization in Indonesia currently faces challenges due to the lack of clear regulation in the existing Patent Law. Addressing this gap presents a valuable opportunity for enhancing the growth of domestic patents and increasing Indonesia’s economic value. There is an urgent need to establish regulations governing patent commercialization, especially in light of South Korea's Invention Promotion Act No. 19495 of 2023, which enhances the protection of inventors' economic rights and promotes economic growth through effective intellectual property development. This study utilizes a normative juridical approach and comparative law to evaluate existing regulatory frameworks and the potential impacts of new patent commercialization regulations on industrial development and innovation. Currently, Indonesia ranks among the countries with the lowest intellectual property indicators in the world. Therefore, it is crucial to implement specific regulations through Government Regulations and Ministerial Regulations that align with the Patent Law to govern patent commercialization. This research highlights the significance of effective law enforcement in promoting patent commercialization as a vital component of national economic development. By applying incentive theory and economic growth stimulus theory, and utilizing economic analysis of law to evaluate policies that promote certainty, equity, and socio-economic benefits for society and the country.